Friction and wear performance of dual lubrication systems combining WS2–MoS2 composite film and low volatility oils under vacuum condition. (July 2016) - Quan, Xin; Hu, Ming; Gao, Xiaoming; Fu, Yanlong; Weng, Lijun; Wang, Desheng; Jiang, Dong; Sun, Jiayi
Abstract: In the present work, WS2 –MoS2 nanocomposite films were sputtered, based on which solid/liquid-lubrication systems were realized by combining the WS2 –MoS2 films with space oils including MACs (multialkylated cyclopentanes) and CPSO (chlorinated-phenyl with methyl-terminated silicone oil). The tribological behaviors of the solid/liquid systems were investigated in vacuum. It was revealed that in comparison to pure WS2 film, the WS2 –MoS2 composite film exhibited an enhanced tribological performance. Moreover, our results identified that the WS2 –MoS2 /MACs system integrated better the advantages of the solid and liquid lubrications and thereby a synergistic lubricating effect was generated. A tribological model was established to explain the synergistic lubricating mechanism. Graphical abstract: Highlights: WS2 –MoS2 nanocomposite films were prepared which exhibited an enhanced tribological performance than pure WS2 films. WS2 –MoS2 /MACs solid/liquid system exhibited excellent tribological properties under vacuum condition. WS2 –MoS2 /MACs system can better unite the advantages of both lubricants to generate synergistic lubricating effect. Tribological mechanism of solid/liquid systems was discussed according to the combination of solid and liquid lubricants.